SPELLING OF CONSONANTS IN THE ROOT OF A WORD - Navruzova Farida Nazarovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article explains in detail the spelling of the word "agree at the root of the word." Also b variant brilliant - brilliant and derivatives Slovak (brilliant - shiny, brilliant - shiny, brilliantin - brilliant) the second members of etix par are written with one letter before.